2016
DOI: 10.1039/c5nj01772f
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and curing kinetics study of a new fluorinated polyurethane with fluorinated side chains attached to soft blocks

Abstract: Fluorinated polyurethane with fluorinated side chains attached to soft blocks was successfully synthesized, which exhibited unique properties. And also the curing kinetics was studied using a rotational rheometer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…The more amorphous PU, the higher its flexibility [26]. As shown in figure 4(a), samples of PU, films exhibited a diffraction peak at approximately 2θ=20°, which was consistent with the results reported in the literature [27,28]. Compared with PU films, the diffraction peak of LPU and MLPU films shifted to higher or lower, which was caused by the complex structure of lignin.…”
Section: Xrd and Dscsupporting
confidence: 88%
“…The more amorphous PU, the higher its flexibility [26]. As shown in figure 4(a), samples of PU, films exhibited a diffraction peak at approximately 2θ=20°, which was consistent with the results reported in the literature [27,28]. Compared with PU films, the diffraction peak of LPU and MLPU films shifted to higher or lower, which was caused by the complex structure of lignin.…”
Section: Xrd and Dscsupporting
confidence: 88%
“…Figure shows the XRD patterns of WPU, WFPU‐6, WFPU‐9 and WFPU‐12. The maximum peak position for all samples was observed near 2 θ = 19° arising from micro‐crystallinity in the hard domains . Moreover, the diffraction patterns were similar.…”
Section: Resultsmentioning
confidence: 67%
“…In comparison to WPU and WFPU‐6, it was observed that the fractured surfaces of WFPU‐9 and WFPU‐12 films obviously presented particles. The formation of particles from the hard segments was associated with the strong hydrogen bonding between CO and NH, which resulted in an increase of microphase separation between the soft and hard segments . With an increase of HTPFMA main‐chain length, stronger hydrogen bonds were formed in hard segments as discussed with the FTIR analysis, leading to an increase of the interaction of hard segments and the formation of more regular shaped particles .…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Under certain conditions, the hard segments in the PU chain segments will aggregate together to form crystalline micro-regions, which can be characterized by X-ray diffraction (XRD). 23,24 Fig. 4a and b presents the XRD patterns of PU and PU-PNIPAm n lms.…”
Section: Preparation Of Pu-pnipam N Composite Materialsmentioning
confidence: 99%